Adaptation of BCCT Learning Model in Developing Religious Aspects of Children - Abd Hamid Wahid; Muhammad Fajri; Hasan Baharun; Riana Imroatul Fitriyah; Arifatur Risqiyah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to find out and analyze the adaptation of BCCT learning models in developing religious aspects of children. With qualitative methods. The informants in the study were principals, class A teachers, and class B teachers taken with a purposive sampling approach. Preliminary observations in the field show that the implementation of early childhood learning still does not entirely refer to the stages of development and growth of children, especially in the religious aspects of children. The results of this study in implementing the BCCT learning model are the first environmental footing by preparing places and conditions before learning. Second, the footing of the experience before playing is also referred to as the opening activity before entering the core learning activities. Third, the footing when playing is the child's activity in playing a role according to the center. Fourth, footing after play is an activity carried out by teachers and children when they finish playing.